2008
DOI: 10.1021/ja8062875
|View full text |Cite
|
Sign up to set email alerts
|

Peptide Imprinted Polymer Nanoparticles: A Plastic Antibody

Abstract: A novel method for preparation of biomacromolecular imprinted nanoparticles is described. Combinations of functional monomers were polymerized in the presence of the imprinting peptide melittin in aqueous solution at room temperature to produce a small library of polymer nanoparticles. The template peptide and unreacted monomers are subsequently removed by dialysis. Nanoparticles (NPs) from the library were evaluated for their binding to melittin by 27 MHz QCM analysis. NPs prepared with optimized functional m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
362
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 389 publications
(364 citation statements)
references
References 22 publications
1
362
0
1
Order By: Relevance
“…However, the combined affinity and specificity of the NPs were not sufficient to detoxify melittin in animal models. Recently, we demonstrated that by applying a molecular imprinting (19) or an affinity purification process (20) together with the combination of functional monomers, NPs with greater affinity to the target peptide was achieved. Furthermore, the NPs with enhanced binding affinity showed neutralization of the toxin in vivo (3).…”
mentioning
confidence: 99%
“…However, the combined affinity and specificity of the NPs were not sufficient to detoxify melittin in animal models. Recently, we demonstrated that by applying a molecular imprinting (19) or an affinity purification process (20) together with the combination of functional monomers, NPs with greater affinity to the target peptide was achieved. Furthermore, the NPs with enhanced binding affinity showed neutralization of the toxin in vivo (3).…”
mentioning
confidence: 99%
“…Figure 3e and f indicate that the surface morphology of the pore structures after adsorption of the NPs were less angulated than the surface morphology before adsorption, although none of the pores were filled by the NPs. The apparent surface roughness of the NPs-immobilized pore surface seemed to be comparable to that of the mono-layered dried NPs films (o10 nm), 10,19,20 suggesting that the surface of GBs were coated with NPs. From those results, it was established that NP-adsorbed macroporous GBs could be prepared simply by incubating negatively charged NPs and positively charged GBs in water.…”
Section: Fusion Of Nano and Micro Gel Materials Y Hoshino Et Almentioning
confidence: 86%
“…[5][6][7][8] Shea and colleagues reported that multifunctional nanogel particles (NPs) polymerized with a combination of functional monomers capture target peptides, 9-12 proteins [13][14][15] and specific domains of proteins 16 via a combination of multipoint electrostatic, hydrophobic, aromatic 17 and/or hydrogen binding 18 interactions. Target affinity can be enhanced by optimizing the feed ratio of functional monomers, 19 by molecular imprinting polymerization 20,21 and/or by affinity purification procedures. 22 It has also been reported that porous membranes polymerized with functional monomers containing carbohydrates can be used as affinity separation media for lectins.…”
Section: Introductionmentioning
confidence: 99%
“…The polymer composition for the preparation of the nanoMIPs was adapted from Hoshino and colleagues. 22 In addition to this, nanoparticles for melamine were prepared in an organic solvent (ACN) by UV polymerisation with and without a PEG shell. In general the interactions between all the imprinted polymers nanoparticles and the different templates were due to a combination of multiple electrostatic and hydrophobic interactions.…”
Section: Synthesis and Characterisation Of Nanomipsmentioning
confidence: 99%
“…18 Recently, several research groups have reported examples of protocols for the synthesis of MIP nanoparticles. [19][20]22 In our case the nanoparticles, which can be produced either in aqueous or organic media depending on the template molecule, exhibit uniform binding sites and high affinity for the target analyte. The main advantage of materials prepared by such solid-phase approach is the possibility to replace directly antibodies with MIPs in standard pseudo-ELISA, with minimal modification of the immobilisation and assay protocol.…”
Section: Introductionmentioning
confidence: 99%